Social Media Marketing Youtube Analysis of Ad Impressions "Tokopedia x BTS: Belanja? Tokopedia Saja!" - Devi Wening Astari (Communicology: Jurnal Ilmu Komunikasi, 2022)
The development of internet-based technology has made many companies do marketing through social media, such as YouTube. The study was conducted to look at the dimensions of social media marketing while at the same time revealing the meaning of sign objects, namely icons, indexes, and symbols as well as discussing the triangle of meaning by involving elements of social media marketing in Tokopedia's advertisements, "Tokopedia x BTS: Belanja? Tokopedia Saja!”. The research uses qualitative methods with Charles Sanders Pierce's semiotic analysis approach. The data was obtained through document studies on the official website, the Tokopedia YouTube channel, and online news media. The data obtained were reduced in sign groups, and tested by triangulation of documentation techniques. Advertisement “Tokopedia x BTS: Belanja? Tokopedia Saja!” contains dimensions of social media marketing, namely: online community, interaction, sharing of content, accessibility, and credibility. In Pierce's semiotic trichotomy analysis, there is an element of meaning from the object, icon, index, and symbol and which contains food in every piece of advertising scene that represents Tokopedia. BTS becomes an icon or sign that represents Tokopedia to be able to spread the values of the Tokopedia brand throughout the world. The index of clothing color, advertising background, and type of writing has represented both parties as a brand that is full of innovation, cheerful, full of enthusiasm, and joy. As well as symbols found as many as 11 symbols, describe and explain well the core message of the advertisement, which is to persuade so that viewers are expected to download the application and then shop online at Tokopedia. It is hoped that in the future, Tokopedia can produce advertisements that are more attractive and can be easily understood by various groups.